INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER DILINGKUNGAN MADRASAH DAN SEKOLAH - Ansori (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2015)
Internalization of Values Character Education is a system of cultivation of character values to the resident of Madrasah and School, which includes knowledge, awareness or willpower, and actions to perform it, either against the Almighty God, ourselves, others, the environment, or nationality to become complete human beings.The values that need to be developed in Education Character in Madrasah and Schools is the peace, respect, compassion, tolerance, honesty, humility, cooperation, happiness, responsibility, simplicity, freedom and unity.The way that is done is always instilled by teachers to their students, by making posters that made the image that corresponds to the theme of the value above, along with a brief word that is easily understood by children or students at school. For example is "The Value of Peace" on the wall of the school or madrasah that made posters. First,create the title of the poster in large letters so can be easy to read, second, create an image of people who are in a peaceful condition, third, create the text below of the picture as: "Peace is Beautiful", “The peace is to have a good feeling in my heart", "Peace is harmony and not fighting or hitting","Peace is positive thoughts about themselves and others","Peace starts from myself". So, if the students walk past the poster indirectly they will understand and absorb the sentences contained in the poster.